Impact of Admixtures on Segregation in Self-compacting concrete: A Comparative Study Between Standardized and Ultrasonic Pulse Velocity (UPV) Methods - Moulaï Abdellah Bouabdallah; Mohamed Mouli; Mohammed Benmammar (The Journal of Engineering and Exact Sciences)
Mastering the rheology of self-compacting concrete (SCC) remains a major challenge for researchers. One of the main obstacles is segregation, an undesirable phenomenon where aggregates separate from the matrix, thus compromising the quality and homogeneity of the material. This study aims to use the ultrasonic pulse velocity (UPV) measurement technique to evaluate the variation in the degree of static segregation in self-compacting concretes. To do so, column-type molds of different sizes were fabricated. The first was designed in accordance with the recommendations of standard V1, while the others, of different dimensions, were made according to standards V2 and V3. The latter allowed the study of the scale effect on the segregation of SCC, by comparing the results with those obtained using UPV. Five SCC mixes, containing respectively 1%, 1.2%, 1.4%, 1.6% and 1.8% of admixture, were tested using standard techniques (sieve and column test), then compared to the results obtained with the UPV method. The experimental results of the two methods were analyzed and compared to other tests, such as spread, L-box, and sieve stability. Moreover, the correlation between the results of the ultrasonic tests and those of the standardized tests (V1, V2, and V3) showed a high coefficient of determination R²: 86% for V1, 92% for V2 and 87% for V3. These results demonstrate that the UPV method is a promising alternative for evaluating segregation of fresh concrete.